Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fchem.2022.833899
|View full text |Cite
|
Sign up to set email alerts
|

A Portable Molecularly Imprinted Sensor for On-Site and Wireless Environmental Bisphenol A Monitoring

Abstract: The detection of pollutant traces in the public and environmental waters is essential for safety of the population. Bisphenol A (BPA) is a toxic chemical widely used for the production of food storage containers by plastic industries to increase the storage ability. However, the insertion of BPA in water medium leads to serious health risks. Therefore, the development of low-cost, practical, sensitive, and selective devices to monitor BPA levels on-site in the environment is highly needed. Herein, for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…A paper-based ion-selective electrode was created by drop-casting 20 L of membrane cocktail. Despite the fact that they used molecularly imprinted nanobeads with a higher affinity for BPA that can well disperse in the polymeric membrane potentiometric sensor, their LOD was lower than that in the studies reported by Ali et al (2019), 39 Tan et al (2016), 40 and Beduk et al (2020) 41 using a MIP-carbon coated electrode. Jemmeli et al (2020) developed a lab on a chip on a paper-based electrochemical sensor for bisphenol A detection 73 in another study (Fig.…”
Section: Methods For Detection Of Emerging Contaminantsmentioning
confidence: 75%
See 1 more Smart Citation
“…A paper-based ion-selective electrode was created by drop-casting 20 L of membrane cocktail. Despite the fact that they used molecularly imprinted nanobeads with a higher affinity for BPA that can well disperse in the polymeric membrane potentiometric sensor, their LOD was lower than that in the studies reported by Ali et al (2019), 39 Tan et al (2016), 40 and Beduk et al (2020) 41 using a MIP-carbon coated electrode. Jemmeli et al (2020) developed a lab on a chip on a paper-based electrochemical sensor for bisphenol A detection 73 in another study (Fig.…”
Section: Methods For Detection Of Emerging Contaminantsmentioning
confidence: 75%
“…Bisphenol A, an endocrine-disrupting chemical widely used in the production of polycarbonate plastics, bottles, food containers, and drinking water bottles, is a major source of great concern. For its detection, 4-VP, acrylamide (AA), N,N 0methylenebis-acrylamide (MBAA), 3-aminopropyl triethoxysilane (APTES), and pyrrole (Py) monomers were used individually and in combination with MWCNTs, and GO on the coated carbon electrode effectively measured bisphenol A in river, drinking, sea and tap water with a LOD of 8-40 nM [39][40][41] (Fig. 3).…”
Section: Electrochemical Based Detectionmentioning
confidence: 99%
“…The mechanism of ligand recognition in the TR has been already reported, in which basic amino acids such as arginine and histidine form hydrogen bonding with the carboxy group and phenol of T3. This recognition mechanism is similar to that of the TRI-MIP, in which basic functional monomers recognize acidic functional groups.…”
Section: Resultsmentioning
confidence: 95%
“…An MIP consists of molecular recognition sites having three-dimensionally located functional monomers that show specific interaction with target compounds and is used as an artificial receptor by imitating real molecular recognition sites. The MIPs are cost-effective and chemically stable. Furthermore, they are suitable for heavily contaminated environmental samples. In fact, commercially available C18 and/or polymer-based adsorbents are utilized for pretreatment of environmental samples, although these adsorbents condense without selectivity via hydrophobic interaction. The samples normally include tons of contaminations, which involve significant interference with detections.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-scribed graphene electrodes (LSGs) have been presented as an alternative for standard screen-printed electrodes (SPEs) due to its electronic properties, large surface area, and high porosity. Recently, Rauf et al demonstrated the improvements that can be achieved by decorating LSGs with gold nanoparticles (AuNPs), followed by other demonstrations of different combinations of nanoparticles in LSGs and their performance improvements in various applications [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%